Ensino médio, currículo e cotidiano escolar : sobre movimentos e tensões nos discursos oficiais - Majeski, Sergio (2013)
This work was motivated by our concern and interest in the issue of education in Brazil, and especially with our empathy with High School. At first we explain the general issues about this educational level, and then we discuss the three most important official policies for high school today: the National Curriculum Guidelines for Secondary Education (DCNEM), the Innovative High School Program (ProEMI) and National Secondary Education Examination (ENEM) focusing on curricular issues and understandings/uses that the practicing subjects make of them in school everyday. Amid questioning these policies are the speeches of teachers and students on the same issues. We try to elucidate the importance that such policies have for the actors of the school everyday and raise questions about the legal framework created by the Ministry of Education and the Department of Education of the State of Espírito Santo. We’ve noticed that most official guidelines are not fully assimilated in school, where practicing subjects adopt their work strategies according to their needs. The questioning of the policies highlighted the growing importance of ENEM, which leads us to believe that over and over all the projects and guidelines for high school will have the influence of this examination